2009
DOI: 10.1097/mcg.0b013e3181919261
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Nonmeckelian Diverticulosis

Abstract: Nonmeckelian jejunoileal diverticula (JID) are rare, but potentially clinically significant lesions. Despite recent advances in modern diagnostic modalities, diagnosis of JID may be problematic. Upper gastrointestinal contrast series with small bowel follow-through examination and mainly enteroclysis are the 2 main diagnostic methods. In selected cases (mainly complicated JID), the physician could use other diagnostic methods, such as ultrasound, computed tomography, endoscopy, intraoperative endoscopy, laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 72 publications
1
107
0
4
Order By: Relevance
“…Jejunal diverticulosis was first defined as herniation of the mucosa and the submucosa from the inside of the muscular layer of the bowel wall on the mesenteric side of the intestine in 1794 by Sommering and later in 1807 by Sir Asley Cooper (1,3). Jejunal diverticula are detected in autopsy series at rates ranging from 1.3% to 4.6%, whereas the rate of radiological detection is between 0.02% and 2.3% (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Jejunal diverticulosis was first defined as herniation of the mucosa and the submucosa from the inside of the muscular layer of the bowel wall on the mesenteric side of the intestine in 1794 by Sommering and later in 1807 by Sir Asley Cooper (1,3). Jejunal diverticula are detected in autopsy series at rates ranging from 1.3% to 4.6%, whereas the rate of radiological detection is between 0.02% and 2.3% (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that some JID may be congenital (solitary diverticula in young patients may represent partial reduplication of the small bowel), it is now widely accepted that most of these lesions are acquired. The pathogenesis seems to be multifactorial (16).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy, radiotagged erythrocyte bleeding scans and selective mesenteric arteriography can be performed as well. Laparotomy remains the gold standard for definite diagnosis of asymptomatic and complicated diverticula (16).…”
Section: Discussionmentioning
confidence: 99%
“…Jejunal diverticula are rare with 1% prevalence in the general population [1]. Small bowel diverticula occur most frequently in the duodenum (45%), followed by Meckel's diverticulum (23%).…”
Section: Introductionmentioning
confidence: 99%